Gesture to Text and Text to Speech Models for Assistance with Speech Impaired People - Ilham Adi Purnamajaya (Universitas Amikom Purwokerto, 2023)
Special Schools in Indonesia are special educational institutions for disabilities. Persons with disabilities, especially the speech impaired, are also in the spotlight in the education sector and need attention. Education for disabilities requires special skills in presenting learning to students with disabilities. The problems that arise in learning for people with disabilities are quite complex. There are not many teachers who are able to provide learning to the speech impaired. They have difficulty with the style of Sign Language used by the speech impaired. This paper will discuss how learning models and techniques for the speech impaired are packaged, the aim is none other than to help teachers present learning for the speech impaired. Standards on teaching materials such as sign language also seem to really need to be done, therefore we first prepared the concept of sign language which will be used as data processing in information for speech-impaired persons. We use in solving this problem using waterfall development, and to complement the data we use literature studies and interviews. The results obtained are in the form of a platform that teachers use as a learning medium for speech-impaired people.